The East Asian Region Confucian Heritage and Its Modern Adaptation. - Rozman, Gilbert (Princeton : Princeton University Press, 2014)
The contributors to this volume range over 2,000 years of history as they show how Confucian values spread throughout the region in premodern times and how these values were transformed in an age of modernization. The introduction by Gilbert Rozman discusses the special character of East Asia. In Part I Patricia Ebrey analyzes the Confucianization of China; JaHyun Kim Haboush, that of Korea; and Martin Collcutt, the much later diffusion of Confucianism in Japan. In Part II Rozman compares types of Confucianism in nineteenth-century China and Japan and their adaptability in the twentieth cen.
Cover; Part I: Confucianization: The Deepening of Tradition; Part II: The Modern Transition: De-Confucianization or Re-Confucianization?
Description based upon print version of record.
Keywords: Philosophy, Confucian -- East Asia; East Asia -- Social life and customs; PHILOSOPHY / Eastern; Electronic books